Penyuluhan Kesehatan Reproduksi Pada Remaja - Destri Maya Rani; Yuli Arinta Dewi; Rina Puspita; Bajeng Nurul Widyaningrum (Akademi Farmasi YPPM Mandiri, 2022)
The period of transition from childhood to adulthood is often referred to as adolescence. During this period, they enter puberty where they experience rapid physical changes, one of which is the ability to carry out the reproductive process. The process of adolescent development is very vulnerable and full of risks, so good personal health is needed. Therefore it is necessary to conduct counseling in an effort to promote and prevent reproductive health problems in adolescence. Because in this period changes and body functions occur in a relatively fast time. It is hoped that the counseling will be aimed at adolescent students representing junior and senior high schools in the city of Semarang. The aim is to increase knowledge about reproductive health and avoid premarital sexual behavior and to know how to handle it properly. It is expected that reproductive health counseling service activities are in accordance with the target.